DEEP LEARNING: ITS SOCIAL IMPLICATIONS - Dr. Mario González Arencibia; Lic. Dagmaris Martínez Cardero (IJRDO - Journal of Social Science and Humanities Research, 2019)
The purpose of this research is to delimit the foundations of "Deep Learning" and its social implications, paying fundamental attention to the analysis of its potentialities for social development. The central idea contained in this paper is that "Deep Learning" is a dual-use technology that can generate both positive and negative implications from human intentionality. This topic is of particular importance because of its methodological and practical value for decision making, which ranges from understanding the new technological change to its application in the different spheres of social reality. In this scenario, data and information converted into knowledge or modes of action to transform reality have become the fuel of the new technological paradigm that emerges from Artificial Intelligence.